Muslim Women’s Perceptions of Barriers to Sectorial Participation: Insights and Clarifications from an Islamic Perspective Based on a Qualitative Study in Ampara District, Sri Lanka - Mohamed Sulthan Ismiya Begum; Indriaty Ismail; Zul’ Azmi Yakoob (Journal of Islam in Asia (E-ISSN 2289-8077), 2024)
Women’s educational attainment and participation in the workforce have increased significantly. However, in the Sri Lankan context, Muslim women often encounter barriers to engaging in professional fields. Although Islam acknowledges the importance of women’s contributions within its ethical framework, many eligible and skilled Muslim women refrain from pursuing careers in essential sectors such as healthcare due to various interpretations of Islamic teachings. This study aims to clarify the historical contributions of Muslim women to professional fields and to investigate the reasons for their current underrepresentation from an Islamic perspective. Using a qualitative research design, purposive sampling was employed to select participants, including housemaids and women in diverse professions from the Ampara District. Data was collected through semi-structured interviews and analysed using content analysis methods. The findings offer valuable insights for women seeking a better understanding of Islamic teaching, academic researchers, advocates for the proper implementation of Islamic principles, and future generations interested in the roles of women within the community.